1982
DOI: 10.1021/ac00249a064
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microgram amounts of asbestos in mixtures by infrared spectrometry

Abstract: The inhalation of asbestos particles has been found to cause a number of serious illnesses among mine workers. The major illnesses, asbestosis and mesothelioma, are caused by the direct inhalation of asbestos fibers into the throat and lungs (1, 2). Other experiments suggest that certain types of asbestos belonging to the amphibole class (amosite, crocidolite, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The FTIR method is still not officially defined. It is well known that different types of asbestos can be identified and quantified by means of FTIR spectroscopy: strong and specific sharp peaks can be found in the absorption spectra in the 4000–400 cm −1 wavenumber region [ 12 , 13 ]. Several studies have demonstrated that FTIR is suitable for the quantification of micrograms of different kinds of asbestos in host matrices, and the FTIR limit of detection could be even less than 1% w / w in the case of bulk samples [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR method is still not officially defined. It is well known that different types of asbestos can be identified and quantified by means of FTIR spectroscopy: strong and specific sharp peaks can be found in the absorption spectra in the 4000–400 cm −1 wavenumber region [ 12 , 13 ]. Several studies have demonstrated that FTIR is suitable for the quantification of micrograms of different kinds of asbestos in host matrices, and the FTIR limit of detection could be even less than 1% w / w in the case of bulk samples [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors report that inhalation of asbestos particles has been found to cause a number of illnesses such as asbestosis (diffuse fibrous scarring of the lungs), pleural plaques (localized fibrous scars lining the space surrounding the lungs), pneumoconiosis, lung cancer (bronchogenic carcinoma) and malignant mesothelioma (malignant tumors arising from the pleural, pericardial, or peritoneal linings). Detailed reports are found in Skinner et al (1988), Luoma et al (1982), and Guthrie (1992). The asbestos variety composed mainly by amphibole minerals are potentially more dangerous than those com-posed by serpentine minerals because of their particle size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of such minerals have also been investigated abundantly by spectroscopic techniques and IR data of each mineralogical species are well documented in the literature (Gasden et al, 1970;Griffiths, 1987;Luoma et al, 1982).…”
Section: Introductionmentioning
confidence: 99%